S134 Pre-EDIT: a randomised, feasibility trial of elastance-directed intra-pleural catheter or talc pleurodesis (EDIT) in the management of symptomatic malignant pleural effusion without obvious non-expansile lung. (December 2018) - Martin, GA; Kidd, AC; Tsim, S; Woodward, R; Hopkins, T; Foster, JE; McLoone, P; Blyth, KG
Abstract : Introduction: Non-expansile lung (NEL) is a common cause of talc pleurodesis (TP) failure in Malignant Pleural Effusion (MPE). NEL is frequently occult prior to drainage and is more effectively managed using an indwelling pleural catheter (IPC). Reliable pre-drainage detection of NEL would facilitate more informed MPE management. Elevated Pleural Elastance (PEL ) is associated with NEL but technical challenges, a limited evidence base and low sensitivity during small volume aspiration have precluded clinical utilisation. Pre-EDIT is a randomised feasibility trial of Elastance-Directed Intra-pleural catheter or Talc Pleurodesis (EDIT) management of MPE, using a novel, purpose-built digital pleural manometer (DPM, Rocket Medical). Methods: EDIT involves computation of PEL during a large volume aspiration. Patients are then directed to TP or IPC within 24 hours (see figure 1). In pre-EDIT, eligible patients (symptomatic MPE, no prior evidence of NEL or preference for IPC) are randomised 1:1 between EDIT and standard care (TP). The primary objective is to determine whether it is feasible to recruit and randomise 30 patients within 12 months (or 15 patients within 6 months). Secondary objectives include assessment of the safety of EDIT management, the aspiration volume required to detect abnormal PEL and the proportion of patients in whom pneumothorax induction is required for subsequent TP/IPC. Additionally, a treatment preferences survey will assess factors important to patients when choosing a first-line intervention for symptomatic MPE. 4-D volumetric pleural Magnetic Resonance Imaging (MRI) is being used to explore mechanisms of symptoms during fluid aspiration, to validate an ultrasound estimate of pleural effusion volume (a proposed inclusion criterion) and the assumption that aspiration volume equals change in pleural cavity volume. Potential MRI biomarkers of NEL will also be explored. Results: 23/30 patients have been recruited at the point of submission. The primary objective was met during 6 months between October 2017 and April 2018. Preliminary results relating to secondary objectives will be available for the Winter BTS Meeting 2018. Conclusion: Pre-EDIT will address important areas of uncertainty regarding the design of a potential future Phase III trial regarding the efficacy of EDIT management. Recruitment has reached a pre-specified feasibility threshold.